THE ANALYSIS OF THE TEXT IN SIBOLGA HISTORY BROCHURE BY USING SISTEMIC FUNCTIONAL LINGUISTIC - Nova Andriani (Journal MELT (Medium for English Language Teaching), 2018)
This Study deals with textual functions in the text of Sibolga History. The objectives of the study were to: (1) describe the types of themes in the text of Sibolga History brochure and (2) identify the social contexts in the text of Sibolga History brochure. This research applied qualitative descriptive design to describe the data analysis. The qualitative analysis was applied in order to find out theoretically related to the research questions. The source of data was the text of Sibolga History brochure which consists of 22 paragraphs. The source was taken through documents that were written in the text of Sibolga History. The data was analyzed by Miles and Huberman model. The theme focused on Topical theme and there are 103 clauses of theme. The text was analyzed with the reference to the theories of Systemic Functional Linguistic (SFL). The finding showed that the proportions are: (1) Marked Simple Theme is 53 %, (2) Marked Multiple Theme is 5%, (3) Unmarked Simple Theme is 41 % and the last (4) Unmarked Multiple Theme wascan not found. It was concluded that the Marked Simple Theme are used in large number and Marked MultipleTheme are used in smaller number. The social context in this text can be seen through the field, tenor and mode of the text of Sibolga History brochure.